2017
DOI: 10.1017/s0033291717000575
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive yoga v. health education for persistent major depression: a randomized controlled trial

Abstract: Background The objective of this study was to determine whether hatha yoga is an efficacious adjunctive intervention for individuals with continued depressive symptoms despite antidepressant treatment. Methods We conducted a randomized controlled trial of weekly yoga classes (n = 63) vs. health education classes (Healthy Living Workshop, or HLW; n = 59) in individuals with elevated depression symptoms and antidepressant medication use. HLW served as an attention-control group. The intervention period was 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 33 publications
4
79
0
Order By: Relevance
“…The mean age was 36.6 years (SD 9.1; range 22.1–50.4). The studies were performed in the United States [ 35 , 79 82 , 86 90 ], India [ 78 , 83 85 , 91 , 92 ], Sweden [ 93 ], and Germany [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age was 36.6 years (SD 9.1; range 22.1–50.4). The studies were performed in the United States [ 35 , 79 82 , 86 90 ], India [ 78 , 83 85 , 91 , 92 ], Sweden [ 93 ], and Germany [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found one study in patients with a chronic major depressive disorder (dysthymia, double depression, and major depressive disorder; defined as having experienced symptoms for over two years, without significant remission of two months or more [ 87 ]), one study in which almost two thirds of the sample had chronic major depression (defined as reporting symptoms over the past two years with absence of remission over two months [ 90 ]), one study in patients with treatment-resistant psychoneurosis or depression (defined as absence of response to conventional treatments, without defining these treatments [ 85 ]) and one study in which the majority of patients (58.33%) had a chronic generalized anxiety disorder (defined as 3–5 years of symptoms [ 83 ]). In one study the sample was described as chronically depressed using the definition of being depressed at least from the onset of pregnancy [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Please see [5] for information about study procedures and CONSORT chart. Briefly, participants were recruited from multiple community sites.…”
Section: Methodsmentioning
confidence: 99%
“…We recently completed a study of 10 weeks of hatha yoga vs. 10 weeks of health education classes as adjunctive interventions for people taking antidepressants who continued to have persistent depressive symptoms(n = 122) [5]. Briefly, we found that although the difference between groups on depression severity was not statistically significant at the end of the 10 week intervention period, differences between groups were statistically significant over the 6-month follow-up time period, favoring yoga.…”
Section: Introductionmentioning
confidence: 99%
“…A Health Education intervention served as the control condition . The duration and timing of these five sessions was identical to the EA condition.…”
Section: Methodsmentioning
confidence: 99%